2017
DOI: 10.1074/jbc.m117.792697
|View full text |Cite
|
Sign up to set email alerts
|

A mutant of the Buthus martensii Karsch antitumor-analgesic peptide exhibits reduced inhibition to hNav1.4 and hNav1.5 channels while retaining analgesic activity

Abstract: Scorpion toxins can kill other animals by inducing paralysis and arrhythmia, which limits the potential applications of these agents in the clinical management of diseases. Antitumor-analgesic peptide (AGAP), purified from Karsch, has been proved to possess analgesic and antitumor activities. Trp, a conserved aromatic residue of AGAP, might play an important role in mediating AGAP activities according to the sequence and homology-modeling analyses. Therefore, an AGAP mutant, W38G, was generated, and effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…These data suggested that rAGAP was successfully produced and correctly refolded in E. coli. Previously, it has been indicated that the W38G mutation in AGAP reduced its activity on Na V 1.4–1.5 channels (Xu et al, ). In our experiment, W38, as well as two other residues (K10 and R58) in AGAP, were mutated, and the effect of the mutations on toxin activity was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggested that rAGAP was successfully produced and correctly refolded in E. coli. Previously, it has been indicated that the W38G mutation in AGAP reduced its activity on Na V 1.4–1.5 channels (Xu et al, ). In our experiment, W38, as well as two other residues (K10 and R58) in AGAP, were mutated, and the effect of the mutations on toxin activity was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…AGAP is an ion channel regulator with diverse activities on a variation of neuronal ion channels such as high-voltage-activated (HVA), low-voltage-activated (LVA) calcium channels as well as tetrodotoxin-resistant (TTX-R) sodium channels [ 16 ]. A total of nine genes (Na v 1.1–Na v 1.9) have been recognized to encode practical sodium channel isoforms [ 8 ]. Na v 1.4 encoded by SCN4A was primarily secreted by skeletal muscle.…”
Section: Bmk Agap and Voltage-gated Channelsmentioning
confidence: 99%
“…It was necessary for the initiation as well as propagation of the action potential necessary for skeletal muscle contraction. On the other hand, Na v 1.3, Na v 1.7, Na v 1.8, and Na v 1.9 have been recognized as potential targets for analgesics [ 8 ].…”
Section: Bmk Agap and Voltage-gated Channelsmentioning
confidence: 99%
See 2 more Smart Citations